Socio-economic conditions of small-scale traditional fishermen: a case study in Payum Village, Merauke District, Papua, Indonesia - Untari; Anggi Chintia Putri Malino; Nina Maksimiliana Ginting; Riza Fachrizal; Rahim Darma; Philipus Betaubun; Andi Adri Arief (Universitas Lancang Kuning, 2021)
Fishermen in Payum Village are still classified as small-scale traditional fishermen and live in the coastal area of ​​Merauke Regency. Their lives depend on the season of fish and shrimp, which causes uncertain income. This study aimed to identify the socio-economic conditions and welfare of local fishermen and non-local fishermen communities in Payum Village, Merauke Regency. The research method used a qualitative descriptive analysis method supported by an analysis of costs, income, and community welfare. The analysis of the social aspects of the education sector of fishermen's families included in family dependents above 70% follow compulsory education, i.e., elementary, junior, and senior high school as well. The health sector of the fishermen receives services from the community health centers (Puskesmas) with free health costs for first aid if they are getting sick. While the economic aspect, for the capital used in human capital and simple fishing gear in dragnets. The income of local fishermen from capture fisheries and shrimp per month is IDR 6,268,991/month and the income of non-local fishermen per year per month is IDR 5,340,403/month. The fishermen's welfare level results using the Fisherman's Exchange Rate (FER) analysis obtained FER values ​​>1, where the FER results for local fishermen were 1.13 and non-local fishermen were 1.48. The study reveals that the level of life of local fishermen and non-local fishermen of coastal Payum, Merauke Regency is at a pretty good level of welfare and can save money.